Standard systems for measurement of pK values and ionic mobilities: 2. Univalent weak bases - Slampová, Andrea; Krivánková, Ludmila; Gebauer, Petr; Bocek, Petr (Journal of chromatography. A, 2009)
This paper contributes to the methodology of measuring pK values and ionic mobilities by capillary zone electrophoresis by introducing the principle of constant ionic strength and minimum interaction of analytes with counterionic components and presenting a standard system of cationic buffers for measurements of weak bases. The system is designed so that all buffers comprise the same concentration of Cl(-) present as the only counter anion. This minimizes problems caused by interactions between the counterion and the analytes which may otherwise bring biased values of obtained effective mobilities. Further, the buffer system provides constant and accurately known ionic strength for an entire set of measurements. When additionally all measurements are performed with constant Joule heating, one correction for ionic strength and temperature is then needed for the obtained set of experimental data. This considerably facilitates their evaluation and regression analysis as the corrections for ionic strength and Joule heating need not be implemented in the computation software and may be applied only once to the final regression results. An experimental example of the proposed methodology is presented and the reliability and the advantages of the proposed system are shown, where the known problematic groups of amines and pyridine were measured with high accuracy and without any notice of anomalous behavior.
Keywords: Chlorine; pufry; Temperature; Electrophoresis, Capillary; chemické modely; Computer Simulation; teplota; termodynamika; alkálie; Alkalies; chlor; osmolární koncentrace; elektroforéza kapilární; Thermodynamics; počítačová simulace; Models, Chemical; anionty; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; Osmolar Concentration; Buffers; Anions